Transformational Leadership and Change: How Leaders Influence Their Followers' Motivation Through Organizational Justice. Issue 3 (May 2016) - Deschamps, Carl; Rinfret, Natalie; Lagacé, Marie Claude; La Capitale, Chaire; Privé, Catherine
Abstract : EXECUTIVE SUMMARY : In the past decade, the reform of Québec's healthcare establishments has resulted in a reduction in the number of institutions through mergers and closures. In this report, we investigate the consequences of reform by looking at managers' motivations and related mitigating factors. We examine the influence that transformational leaders have on their employees' motivation through organizational justice. Using a survey of 253 healthcare managers, we describe how the positive impact of transformational leadership on motivation is fully mediated via different aspects of organizational justice. The results indicate that while transformational leaders influence each type of organizational justice, followers' motivation is affected primarily by procedural and interpersonal justice and little by distributive justice.